The Last Ring Lady - Hakimi, Halim (UNIMAS Publisher, 2024)
Wanita Gelang Semban represents and invaluable treasure of Sarawak. Currently, only five individuals remain as the Last Ringed Women of Bidayuh community in Sarawak. This work unveils the story of the youngest ringed woman, who serves as the torchbearer for this priceless heritage of Sarawak and Malaysia.